Prenatal diagnosis and outcome of fetal urinomas in relation to the underlying etiology - Simonini, Corinna; Strizek, Brigitte; Strömer, Annika; Gembruch, Ulrich; Geipel, Annegret (Prenatal Diagnosis, 2023)
AbstractObjectiveEvaluation of course and outcome of pregnancies with prenatally diagnosed fetal urinoma in a single center over a 20‐year period.MethodsRetrospective study including all prenatally suspected or diagnosed fetal urinomas. Cases were analyzed by ultrasound findings during pregnancy, comparing urinomas caused by lower urinary tract obstruction (LUTO) and ureteropelvic or ureterovesical junction obstruction (UPJO/UVJO). Course of pregnancy and outcomes were compared according to the underlying etiology.Results87 cases of fetal urinomas were identified between 2002 and 2022. The underlying etiology was LUTO in 56.3% and UPJO/UVJO in 43.7%. Complications mainly included oligo‐ or anhydramnios, thoracic hypoplasia as well as associated renal abnormalities. Postnatally, loss of function (LOF) in kidneys affected by urinomas was seen in 78.6% of children overall, but significantly more often in cases of UPJO/UVJO than in LUTO (86.2% vs. 70.2%, p < 0.05).ConclusionAssociation of prenatal urinoma and postnatal LOF of the affected kidney is high, especially in cases caused by UPJO/UVJO. In survivors with urinoma caused by UPJO/UVJO, the general prognosis is excellent if the contralateral kidney was normal. In survivors with urinomas caused by LUTO, long‐term prognosis depends on postnatal renal and pulmonary function.